Corporatizing a Water Utility : A Successful Case Using a Performance-Based Service Contract for ONEA in Burkina Faso - Marin, Philippe (World Bank, Washington, DC, 2012)
Thanks to a corporatization process spanning two decades, Burkina Faso's national water and sanitation utility ranks among the few well-managed public water utilities in Sub-Saharan Africa. Key to its success has been the government's unceasing commitment to reform, which included the successful implementation of an innovative performance-based service contract with an international operator from 2001 to 2006. The experience shows that it is possible to establish a well-performing public water utility in a poor developing country- as long as the governance framework ensures the autonomy and accountability of the service provider and the government supports the sector's long-term financial viability through an appropriate tariff and investment policy.